Numerical Analysis Finite Element Method of Settlement on Soft Soil, Case Study: National Road of Bts. Kota Sidoarjo – Gempol KM 31+150, Porong, East Java - Delfian, Yopi; Andiek Maulana, Mahendra; Desa Warnana, Dwa; Artoto, Apri (Journal of Infrastructure & Facility Asset Management, 2025)
National Road of Section Bts. Kota Sidoarjo – Gempol is an important access for road users in East Java. A volcanic mud eruption, Lumpur Sidoarjo (Lusi) in 2006 impacted economic and social factors, especially the infrastructure around Lusi. Differential settlement occurs from the research site at the lowest elevation road surface (KM 31+350) near the P10.D levee. This problem affects the level of road safety. it is necessary to analyze settlement to determine the causes of land subsidence in that location. Identification of soft soil condition based on SPT data of BH-2 (west side) and BH03 (east side). Finite Element Method (FEM) numerical analysis is carried out by modeling from the levee to the main road. FEM results showed that vertical deformation (Uy) on the main road is -9,904 cm. FEM results showed that vertical deformation on the levee at 122 days consolidation is 18,27 cm. 19,30 cm vertical deformation from April 2020 – August 2020 (122 days) based on elevation measurements P10D levee’s elevation. Based on laboratory test data, BH-2 location depth >-4,45 m are soft clay conditions expect at a depth of 10,45 m which are silty sand soils. BH-3 location depth > -6,45 m are soft clay conditions. FEM results show that the embankment of the levee affects road deformation. Based on a comparison of FEM analysis with embankment deformation data, it can be used as a reference for land subsidence analysis on the road.